Perception, prevalence and factors associated to school bullying in young people from a population affiliated in a colombian health subsidized insurance company in 2018. (2020)
Describe the perception from young people about bullying, the prevalence of this event and explore the factors associated with being a victim. A retrospective cohort (2014-2018) was followed by a health insurer company of the subsidized regime in Colombia. The study sample consisted of 35,214 young people aged 10-24 years living in 21 municipalities of the Colombian Caribbean region. Means and standard deviation were expressed for continuous variables and frequencies for categorical variables. For the associated factors, a logistic model was estimated using as explanatory variables, sex, housing area, age range, family functionality, disability of the young person, disability of a family member and variables of psychological perception. 63.6% of young people answered that they have knowledge about what school bullying is, noting that as the schooling of the young person increases, the higher the proportion of positive response. The physical or verbal school bullying rate was 94 young people per 1,000. It was found that factors such as the youth feeling useless and guilty (OR = 3.14, p = 0.000), attending psychological counseling (OR = 1.78, p = 0.000), repeating years (OR = 1.49, p = 0.000), that the young person has a disability (OR = 1.33, p = 0.004), or a family member has a disability (OR = 1.27, p = 0.000), is associated with being a victim of bullying. Likewise, it was found that belonging to a highly functional family environment (OR = 0.57, p = 0.000) is a protective factor. School bullying is an event that needs attention and requires supervision of all those around young people, in order to avoid changes in behavior or suicide. Therefore, health systems must offer comprehensive care to prevent mental health risks related to bullying given their relationship with the presence of disability of the young person or a relative